COMPLETE ORGANIZATION STRUCTURE ACCORDING TO THE MULTI-DISCIPLINARY AND MULTI – SECTOR MANAGEMENT MODEL IN VIET NAM – IN CASE OF MINISTRY OF HOME AFFAIRS OF VIET NAM - Dao, Thuy Thi Thanh (Advances in Social Sciences Research Journal, 2019)
Previously, Vietnam applied the model of state organization which was same to model of socialist countries in Eastern Europe and each sector established a ministry or equivalent ministry to manage so government apparatus is quite cumbersome. In 1981, the Government of Vietnam in the 7th term has 27 ministries, 6 committees, Government Office and 27 Government department. From 8th term (1986 – 1991), Viet nam began to focus on researching and applying the multi-disciplinary and multi-sector management model for some ministries such as Ministry of Agriculture and Food Industry; Ministry of Energy; Ministry of Labor, Invalids and Social Affairs. On the basis of implementing the Law on Government Organization which was amended in 2001 (the Law on Government Organization was revised in 2015), The Government in the 11th term has merged a number of Government units into ministries to reduce organizations that are directly under the Government. However, when Government merged units into some ministries, the ministries received the status quo which were not arranged, reorganized the apparatus, re-arranged officials and settled regimes, policies. So far, Vietnam has not had a summary of lessons to evaluate the organization model. Therefore, this paper has done research on issues related to organizational structure of the Ministry according to multi - disciplinary and the multi – sector management model with objects are state management units and non-business units of the Home Affairs in order to meet the requirements in organizational reform of the Vietnam Government. The author’s research uses Ministry of home affairs of Vietnam’s statistics. Besides, the paper use Sociological survey with officials working at departments, institutes, research institutes, training schools and units of Ministry of home affairs of Vietnam, using a questionnaire with 71 leaders and officials. These research data are the survey results of the group of Home office’project, chaired by the National Academy of Public Administration. And the author is the team leader who conducts a status at units of Home office.